2017
DOI: 10.1515/fas-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Fatigue Crack Growth in the Paris Regime under the Variability of Cyclic Hardening and Elastic Properties

Abstract: Over the last 60 years, several models have been developed governing different zones of fatigue crack growth from the threshold zone to final failure. The best known model is the Paris law and a number of its based on mechanical, metallurgical and loading parameters governing the propagation of cracks. This paper presents an analytical model developed to predict the fatigue crack propagation rate in the Paris regime, for different material properties, yield strength (σy), Young’s modulus (E) and cyclic hardeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…where a is the length of the crack, N is the number of cycles, C is the Paris constant, and m is the Paris exponent. Both C and m are dependent strongly on the cyclic hardening exponent and mechanical properties [42], and they are obtained experimentally. Several authors [43,44] identified a very consistent empirical relationship between Paris' law parameters, which was supported by experimental results, such as [45,46].…”
Section: Mixed-mode Fatigue Life Evaluation Proceduresmentioning
confidence: 79%
“…where a is the length of the crack, N is the number of cycles, C is the Paris constant, and m is the Paris exponent. Both C and m are dependent strongly on the cyclic hardening exponent and mechanical properties [42], and they are obtained experimentally. Several authors [43,44] identified a very consistent empirical relationship between Paris' law parameters, which was supported by experimental results, such as [45,46].…”
Section: Mixed-mode Fatigue Life Evaluation Proceduresmentioning
confidence: 79%
“…This observation suggests as a physical interpretation that the growth rate of cracks is significantly influenced by the cyclic strain hardening characteristics at the material crack tip. This phenomenon has been extensively studied in literature through analytical efforts as well as experimental results, and it has been found to have a direct impact on FCGR [25][26][27]65 and has been associated with the crack closure phenomenon. 66 Furthermore, Equation ( 25), considering the stress ratio effect, may be appropriately modified to also include the residual stresses effect in FCGR analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The values of 'm' and 'C' are listed in table 1. The value of 'm' is crucial in determining the fatigue crack resistance [23][24][25]. The corresponding modeling equations for selected C(T) samples are shown as equations (5) to (8).…”
Section: Fatigue Crack Growth Behavior With Different Notch Locationsmentioning
confidence: 99%